Domain-Specific Aspects of Technological Pedagogical Content Knowledge: Music Education and the Importance of Affect - Macrides, Elena; Angeli, Charoula (TechTrends, 2018)
The present study addresses the lack of a theoretical framework for the integration of technology in music teaching and learning, and explores, within the framework of Technological Pedagogical Content Knowledge (TPACK), the importance of affect in the instructional design of music lessons. The purpose of this study is twofold: (a) to extend the theoretical framework of TPACK to a design framework by enriching it with domain-specific design guidelines for the teaching of music, and, (b) to identify and propose design guidelines, which can facilitate associations of affect with cognition in learning music with technology. The research has practical significance for teachers and practitioners as it provides explicit instructional design guidance of how music lessons can be designed based on TPACK principles that address both the cognitive and the affective domain.